Aerodynamics: a different perspective with profound implications - Adam B. Suppes; Galen J. Suppes (Frontiers in Mechanical Engineering)
An increased rigor in the fundamental mechanisms of how air flow generates lift teaches toward a new type of ground effect aircraft referred to as ground effect flight transit (GEFT). While GEFT have lower underbody cavities similar to hovercraft, the pressure field is generated by oncoming air flow with the result of improved energy efficiency in both lift generation and drag reduction as based on computational fluid dynamics studies. The result is a new intermodal transportation with the prospect of higher speeds and efficiency than trucks and trains. The technology will utilize existing railway and highway infrastructure. The prospect includes a significant expansion of capabilities for electric vehicles with advantageous environmental impact and reduced reliance on petroleum-based fuels.